Human rights: An analysis from the perspective of persons deprived of liberty in Ecuador - Ortega-Galarza, Máximo; Altamirano-Pérez, Hólguer Rodrigo; Pachacama-Socasi, Víctor; Coloma, Kathrina Samira Ortega; Coloma, Máximo Leonid Ortega (Seven Editora, 2023)
Persons deprived of liberty and under the protection of the State are in a situation of special vulnerability, and the frequent lack of public policies in this regard has meant that the conditions in which these persons are held are characterized by the systematic violation of their human rights. This article aims to explain the importance of human rights guarantees for persons deprived of liberty (PPL) in Ecuador. Key challenges to the rights of detainees, such as violence, lack of basic services and discrimination, were mentioned. The methodology proposed in the descriptive type of research, was based on a mixed approach where the importance of national and international legal instruments in the protection of the rights of detainees was highlighted and some of them were mentioned, such as the Constitution of Ecuador and the International Covenant on Civil and Political Rights, therefore, it is essential that States adopt concrete measures aimed at addressing these structural deficiencies. DOI:https://doi.org/10.56238/sevened2023.006-092